Hypofractionated Radiotherapy in Combination With Chemotherapy Improves Outcome of Patients With Esophageal Carcinoma Tracheoesophageal Groove Lymph Node Metastasis - Wang, Jian; Yu, Jingping; Jiang, Youqin; Pei, Dong; Zhu, Haiwen; Wang, Jianlin (Frontiers in Oncology, 2020)
This study investigated the efficiency and safety of hypofractioned radiotherapy (HFR) combined with paclitaxel chemotherapy for the treatment of post-surgery tracheoesophageal groove lymph node (TGLN) metastasis in patients with esophageal cancer (EC). Fifty-three EC patients with TGLN metastasis after surgery admitted to the Yancheng Third People’s Hospital from January 2013 to June 2015 were included in this study. They were randomly divided into HFR group (n=25) and conventional fractioned radiotherapy (CFR) group (n=28) based on the random grouping method. Patients in HFR group received treatment with radiation of 60 Gy (5 fractions per week, total 20 fractions) combined with paclitaxel chemotherapy at a dose of 50 mg once per week for 4 weeks. Patients in CFR group received radiation of 60 Gy (5 fractions per week, total 30 fractions) combined with paclitaxel chemotherapy at a dose of 50 mg once per week for 6 weeks. The adverse events and treatment outcomes in these two groups were analyzed. It was found that there was no significant difference in the incidence of radiation esophagitis in the HFR group compared with that of the CFR group (grade 3-4 44.0% vs. 25.0%, P=0.149). There was no statistical difference in the incidence of radiation pneumonitis between these two groups (grade 3-4, 16.0% vs. 7.1%, P=0.314). No statistical difference was noticed in complete response (CR), partial response (PR), and no response (NR) between thees two groups. The median overall survival (OS) in the HRF group was significantly longer compared with that of the CRF group [24.2 months (95%CI: 16.2-32.1 months) vs. 11.8 months (95%CI: 9.2-14.4 months), P=0.024]. Our results indicated that the combination of HFR and chemotherapy improved the prognosis of EC patients with TGLN metastasis with no increased adverse events.